Kecemasan sosial dewasa awal: Adakah peran kecenderungan kecanduan media sosial dan body dissatisfaction ? - Aslamiyah, Farikha; Santi, Dyan Evita; Ananta, Aliffia (JIWA: Jurnal Psikologi Indonesia, 2024)
Abstract This research aims to determine the relationship between social media addiction tendencies and body dissatisfaction with social anxiety in early adulthood. Social anxiety refers to the behavior of withdrawing from social environments, referring to nervous behavior when meeting other people. This research used quantitative methods involving a population of 81,790 students who were studying at tertiary institutions in Sukolilo District involving 12 universities. The research subjects consisted of 271 early adult students, aged 18-25 years, who were selected by accidental sampling. Data were collected using a Likert scale, with instruments using the social anxiety scale of La Greca & Lopez theory, the social media addiction tendency scale of Griffiths theory, and the body dissatisfaction scale of Rosen & Reiter theory. Multiple linear regression analysis shows that there is a simultaneous relationship between social media addiction tendencies and body dissatisfaction with social anxiety. Partially, a positive relationship was found between the tendency to be addicted to social media and social anxiety, as well as body dissatisfaction and social anxiety. Keywords: Social anxiety; social media addiction tendencies; body dissatisfaction Abstrak Penelitian ini bertujuan untuk mengetahui adanya hubungan antara kecenderungan kecanduan media sosial dan body dissatisfaction dengan kecemasan sosial pada dewasa awal. Kecemasan sosial merujuk pada perilaku menarik diri dari lingkungan sosial, merujuk pada perilaku gugup bertemu orang lain. Penelitian ini menggunakan metode kuantitatif dengan melibatkan populasi sebanyak 81.790 mahasiswa yang sedang menempuh perguruan tinggi di Kecamatan Sukolilo dengan melibatkan 12 Universitas. Subjek penelitian terdiri dari 271 mahasiswa dewasa awal, berusia 18-25 tahun, yang dipilih secara accidental sampling. Pengumpulan data menggunakan skala likert, dengan instrument menggunakan skala kecemasan sosial teori La Greca & Lopez, skala kecenderungan kecanduan media sosial teori Griffith, dan skala body dissatisfaction teori Rosen & Reiter. Analisis regresi linear berganda menunjukkan bahwa terdapat hubungan simultan antara kecenderungan kecanduan media sosial dan body dissatisfaction dengan kecemasan sosial. Secara parsial, ditemukan hubungan positif antara kecenderungan kecanduan media sosial dan kecemasan sosial, serta body dissatisfaction dengan kecemasan sosial. Kata kunci: Kecemasan sosial; kecenderungan kecanduan media sosial;body dissatisfaction